Designing a software for qualitative and quantitative analysis of oropharyngeal swallowing by videofluoroscopy - Silva, A.; Santos, R.; Silva, R. [UNESP]; Coimbra, M. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Swallowing is a dynamic, complex and synergistic process, composed of three phases with a refined neuromotor control. A malfunction of this process, denominated dysphasia, can occur in any age like a result of congenital, structural, functional and/or medical problems. The quantitative analysis of this process is crucial to understand the temporal relations between the mechanisms of the oropharyngeal deglutition. Designing a software to support the qualitative and quantitative analysis of the swallowing process through dynamic images obtained by videofluoroscopy is the main motivation and objective of this work. First, a survey of requirements for such a software was made, consisting in a research protocol for assessing dysphagia by videofluoroscopy. Secondly, best practices in humancomputer interaction were used to design a conceptual model for the proposed software. Two protocols were selected for the assessment of dysphagia by videofluoroscopy: the Protocol of Boston and the Protocol used in the Hospital Privado da Trofa. These protocols allowed the identification of several events that are evaluated in the swallowing process and that can be recorded, measured and quantified during ingestion of the bolus. The second phase resulted in a conceptual model for an interactive system embodying the evaluation protocol selected and contemplates the integration of automatic algorithms for qualitative and quantitative evaluation of the parameters of swallowing. The proposed software model has a high potential to be a useful tool for assessing parameters of swallowing.